Modulation of caseinate-stabilized model oil-in-water emulsions with soy lecithin. (August 2019) - Chung, Cheryl; Koo, Charmaine K.W.; Sher, Alexander; Fu, Jun-Tse R.; Rousset, Philippe; McClements, David Julian
Abstract: Demands for plant-based food and beverage products have escalated in recent years. However, many commercial coffee creamers are still being made using dairy derivatives such as sodium caseinate. Therefore, there is a need to investigate the replacement of dairy based proteins with plant-based alternatives. This study was carried out to systematically investigate the properties of model O/W emulsions stabilized by either sodium caseinate (0.25 to 1.5%) or soy lecithin (0.5 to 1.5%). The model emulsions were made of 10% medium chain triglyceride (MCT) oil-in-water emulsions at pH 7. All model O/W emulsions exhibited whitish appearances similar to that of commercial creamers and were effective at lightening black coffee, except those containing the lowest emulsifier concentrations i.e., 0.25% caseinate or 0.5% lecithin. The lightness of the model emulsions depended on the type and level of emulsifier used, with soy lecithin-stabilized emulsions having similar lightening power compare to that stabilized by sodium caseinate. No feathering or free oil were observed in the whitened coffees at the highest emulsifier level used. Mixtures of caseinate and lecithin emulsifiers were also used and model O/W emulsions with similar physical properties to that stabilized by sodium caseinate alone were produced. The mixed emulsifier-stabilized model emulsions had similar lightness when added to coffee than those stabilized by the individual emulsifiers, suggesting similar stabilization mechanisms using these emulsifiers alone or in combination. Graphical abstract: Unlabelled Image Highlights: Demands for plant-based milk and creamer products have escalated recently. Model creamers were fabricated using soy lecithin and/or sodium caseinate These creamers had similar physical properties to conventional dairy-based creamers. The creamers were stable to aggregation and feathering after added to hot, acidic coffee.